1999
DOI: 10.1111/j.1572-0241.1999.883_l.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of Substance P in The Pathogenesis of Spider Angiomas in Patients With Nonalcoholic Liver Cirrhosis

Abstract: Plasma levels of substance P are elevated in patients with nonalcoholic cirrhosis and may play an important role in the pathogenesis of spider angiomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
16
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 33 publications
1
16
0
Order By: Relevance
“…In Cos cells, phosphorylation-deficient cyclin B1 protein is cytoplasmic; in contrast, mutation of all four serines to mimic constitutive phosphorylation (Ser to Glu) drives cyclin B1 into the nucleus. Moreover, appending a strong nuclear localization signal (NLS) to the phosphorylation-deficient cyclin B1 restored its ability to promote oocyte maturation (4). Consistent with these observations, we reported that mutation of all four serines to Glu impaired the ability of the CRS to bind to the nuclear export factor CRM1 and prevented cyclin B1 nuclear export, thus facilitating nuclear accumulation of cyclin B1 complexes at the G 2 /M transition (3).…”
supporting
confidence: 55%
“…In Cos cells, phosphorylation-deficient cyclin B1 protein is cytoplasmic; in contrast, mutation of all four serines to mimic constitutive phosphorylation (Ser to Glu) drives cyclin B1 into the nucleus. Moreover, appending a strong nuclear localization signal (NLS) to the phosphorylation-deficient cyclin B1 restored its ability to promote oocyte maturation (4). Consistent with these observations, we reported that mutation of all four serines to Glu impaired the ability of the CRS to bind to the nuclear export factor CRM1 and prevented cyclin B1 nuclear export, thus facilitating nuclear accumulation of cyclin B1 complexes at the G 2 /M transition (3).…”
supporting
confidence: 55%
“…As shown recently in the case of MADR2, its nuclear accumulation and signaling depend on it being phosphorylated (35). This does not appear to be an isolated case as more and more instances are being reported on the influence of protein phosphorylation on the cellular location of various proteins (34,36,37), particularly those associated with cell division. It is interesting to note that only the nuclear form of dUTPase is also phosphorylated (33).…”
Section: Discussionmentioning
confidence: 82%
“…This shows that cyclin B phosphorylation is not essential for the catalytic activity of the complex and confirms similar data obtained indirectly (mutation of phosphorylation sites) in goldfish (29) and Xenopus (33) oocytes. Studies from Li et al (33,34) have shown the requirement of cyclin B 1 phosphorylation for nuclear localization and Xenopus oocyte maturation. Nuclear localization of cyclin B 1 is regulated by its phosphorylation at sites within the cytoplasmic retention signal domain (34,48).…”
Section: Discussionmentioning
confidence: 99%
“…Studies from Li et al (33,34) have shown the requirement of cyclin B 1 phosphorylation for nuclear localization and Xenopus oocyte maturation. Nuclear localization of cyclin B 1 is regulated by its phosphorylation at sites within the cytoplasmic retention signal domain (34,48). Phosphorylation of cyclin B 1 masking the cytoplasmic retention signal would therefore permit migration into the nucleus, allowing phosphorylation of nuclear substrates by MPF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation